Pengaruh Sustainability Reporting terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Moderasi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Kusumawati, Muhammad Dhoifulloh; Nawangsari, Ajeng Tita (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study examines the influence of sustainability reporting on firm value and investigates whether good corporate governance strengthens this relationship. Using secondary data from non-financial companies listed on the Indonesia Stock Exchange, the analysis applies a quantitative approach with a moderating regression model. The findings indicate that sustainability reporting has a positive effect on firm value, suggesting that investors increasingly consider non-financial disclosures as relevant information in evaluating long-term business prospects. Good corporate governance also shows a positive association with firm value, reflecting the importance of internal monitoring mechanisms in enhancing the credibility of corporate information. Furthermore, the moderating analysis demonstrates that good corporate governance reinforces the impact of sustainability reporting on firm value. Companies with stronger governance structures tend to gain greater market appreciation for their sustainability disclosures. Overall, this study highlights the need for companies to integrate transparent sustainability practices with effective governance systems to maximize value creation and strengthen investor confidence.